2015
DOI: 10.1182/blood-2014-09-598763
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab vedotin demonstrates objective responses in a phase 2 study of relapsed/refractory DLBCL with variable CD30 expression

Abstract: • Brentuximab vedotin was active in DLBCL across a range of CD30 expression levels, and objective responses occurred in 44% of patients. . There was no statistical correlation between response and level of CD30 expression; however, all responding patients had quantifiable CD30 by computerassisted assessment of immunohistochemistry. DLBCL patients were generally refractory to first-line (76%) and most recent therapies (82%), and 44% of these refractory patients responded (15% CRs). Patients with other B-cell ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
203
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(222 citation statements)
references
References 32 publications
9
203
2
8
Order By: Relevance
“…To date, four studies have already addressed this issue and failed to demonstrate any correlation between response to BV and the level of CD30 expression on tumor cells. 4,5,6,10 In the previous report on systemic non-ALCL PTCL, 4 more than 80% of the cases featured no or low levels of CD30 expression (<25% of CD30 + tumor cells), and as in our study, some patients with only a weak CD30 expression on tumor cells responded to BV, raising the question of the mechanism of BV action in these cases. However, the heterogeneity of CD30 expression in our population highlights the likelihood for better response for patients with strong CD30 expression by tumor cells.…”
Section: Letters To the Editormentioning
confidence: 48%
See 1 more Smart Citation
“…To date, four studies have already addressed this issue and failed to demonstrate any correlation between response to BV and the level of CD30 expression on tumor cells. 4,5,6,10 In the previous report on systemic non-ALCL PTCL, 4 more than 80% of the cases featured no or low levels of CD30 expression (<25% of CD30 + tumor cells), and as in our study, some patients with only a weak CD30 expression on tumor cells responded to BV, raising the question of the mechanism of BV action in these cases. However, the heterogeneity of CD30 expression in our population highlights the likelihood for better response for patients with strong CD30 expression by tumor cells.…”
Section: Letters To the Editormentioning
confidence: 48%
“…Mathilde Lamarque, 1,2,3 Céline Bossard, 4 Adrien Contejean, 5,6 Pauline Brice, 6 Marie Parrens, 7 Steven Le Gouill, 8,9 Josette Brière, 10 Reda Bouabdallah, 11 …”
Section: 1112unclassified
“…Importantly, another phase II clinical trial proved the efficacy of brentuximab vedotin in CD30-positive non-Hodgkin lymphoma with lower CD30 expression levels. The objective response rate in CD30-positive diffuse large B-cell lymphoma was 44% (13). Moreover, this study concluded that brentuximab vedotin can be combined safely with rituximab for simultaneous treatment of CD20-positive lymphomas.…”
mentioning
confidence: 71%
“…Clinical studies have also highlighted the lack of precise quantification methods to estimate CD30 expression in lymphomas as a current impediment to optimum patient management (11)(12)(13)(14). At present, it remains unclear whether there exists a threshold level of CD30-positive lymphoma cells that is required for effective brentuximab vedotin treatment.…”
mentioning
confidence: 99%
“…Fázis II. klinikai vizsgálatban refrakter/relabáló DLBCL esetén a brentuximab vedotin (ADCETRIS) monoterápia kedvező eredményeket mutatott [46]. Az eredmények alapján további vizsgála-tok indulnak a brentuximab vedotin kombinációs kezelés alkalmazásával DLBCL első vonalban is.…”
Section: A Dlbcl Kezelése Maunclassified